Examinations on the air quality in Berehove (Beregszász, Ukraine) between 1997 and 2007 - Papp, Géza (Acta Geographica Debrecina Landscape & Environment series, 2008)
First results of the examinations on the air quality in Beregszász (Ukraine) are presented in the present paper. Data sets of air quality monitoring network in Beregszász were provided by the Beregszász township office of National Health Service of Ukraine. Monitoring network consists of five stations in the industrial residential and recreational districts of the town. Measurements were carried out between 1995 and 2007 in the heating and in the non heating seasons. Spatial and seasonalű distributions of SO2, NO2 and particulate matter were analyzed using the Student t-test.